BIMBINGAN PADA ANAK BERHADAPAN HUKUM DALAM MENGHADAPI KECEMASAN SAAT SIDANG PENGADILAN DI BALAI PERLINDUNGAN DAN REHABILITASI SOSIAL REMAJA YOGYAKARTA, INDONESIA - Nanang Pramono; Galih Fajar Fadillah; Anni Nurul Hidayati (Pusat Studi Gender dan Anak, 2022)
The Yogyakarta Social Protection and Rehabilitation Center for Youth (BPSRR) is a place for safeguarding children in conflict with the law. Children who violate the law must undergo a rehabilitation process. However, before carrying out rehabilitation, some functions must be passed, especially the court process determining how long the child will be in repair. This article examines the process of assisting children in conflict with the law. The type of research used by researchers is qualitative research, with a descriptive approach. Data collection techniques in this study were observation and interviews with two social workers, two social workers, and two children dealing with the law and documentation. Using interactive analysis and the triangulation method, it can be seen that the guidance process in assisting children in conflict with the law when carrying out a trial has five stages: the assessment is the initial data stage from children in conflict with the law. Then the second stage is an adaptation in the hostel for children in conflict with the law related to their mental condition. The third stage of the trial guidance process is the direction given by social workers to children in conflict with the law in the trial process that will be carried out. Usually, children are worried because they are unaware of the trial process. Stage four is the individual handling process. In this process, the child experiencing downtime is concerned about personal handling. The fifth stage of group counseling helps children in conflict with the law share experiences with the trial process that is being carried out so that ABH feels better prepared to face the trial.